Risk factors affecting mortality in pediatric heart transplantation: A comprehensive review of pre- and post-transplant contributors - Sydney Elizer, MD; Benjamin S. Mantell, MD, PhD, Assistant Professor of Pediatrics (JHLT Open)
Pediatric heart transplantation (HT) has transformed outcomes for children with end-stage heart failure. Despite advances in surgical techniques and immunosuppressive strategies, mortality remains influenced by numerous risk factors. This review consolidates current literature on pre- and post-transplant variables affecting mortality in pediatric HT, focusing on donor, recipient, and environmental contributors. Pertinent adult studies are also incorporated to highlight overlapping considerations. Recognition of these factors is critical to improving graft survival and long-term outcomes. Key pre-transplant elements include repeated sternotomies, high pulmonary vascular resistance, and extremes of body mass index, while post-transplant issues such as infection, rejection, and cardiac allograft vasculopathy (CAV) remain pivotal. Social determinants of health further modulate survival, reflecting the multifaceted nature of pediatric HT outcomes. By synthesizing existing data, this review aims to provide a framework for identifying high-risk profiles in pediatric HT recipients.